RANCANG BANGUN APLIKASI GAME EDUKASI BERBASIS MOBILE UNTUK MATA PELAJARAN IPA TENTANG SISTEM PENCERNAAN MANUSIA UNTUK KELAS V SDN MADYOTAMAN TAHUN AJARAN 2024/2025 - Risdan Ardiansyah; Hera Heru Sri Suryanti; Moenawar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the feasibility and teacher responses toward amobile-based learning media called Digest Game in the science subject, specificallythe human digestive system material for fifth-grade students at SD NegeriMadyotaman. The research employed a Research and Development (R&D) methodusing the ADDIE model, which includes the stages of analysis, design,development, implementation, and evaluation. Data were collected throughinterviews, questionnaires, and documentation, and were validated by subjectmatter experts, media experts, and teachers. In addition, pre-tests and post-testswere conducted on students, along with black-box testing to ensure the application'sfunctionality. The results indicate that the Digest Game application is feasible to beused as an interactive learning medium. The feasibility assessments were 87% fromsubject matter experts, 80% from media experts, and 91% from teachers — allcategorized as "highly feasible."